Cranial Pathologies in a Specimen of Pachycephalosaurus - Peterson, Joseph E. (Public Library of Science, 2012)

(untitled)
BACKGROUND: A frontoparietal dome of a large pachycephalosaurid collected from the Upper Cretaceous Hell Creek Formation in 2001 is identified as Pachycephalosaurus wyomingensis. The specimen features two large oval depressions on the dorsal surface, accompanied by numerous circular pits on the margin and inner surface of the larger depressions. METHODOLOGY/PRINCIPAL FINDINGS: In order to identify the origin of these structures, computed tomography (CT) data and morphological characteristics of the specimen are analyzed and compared with similar osteological structures in fossil and extant archosaurs caused by taphonomic processes, non-pathologic bone resorption, and traumatic infection/inflammatory origins. The results of these analyses suggest that the structures are pathologic lesions likely resulting from a traumatic injury and followed by secondary infection at the site. CONCLUSIONS/SIGNIFICANCE: The presence of lesions on a frontoparietal dome, and the exclusivity of their distribution along the dorsal dome surface, offers further insight into frontoparietal dome function and supports previously hypothesized agonistic behavior in pachycephalosaurids.